Peer facilitated writing groups: a programmatic approach to doctoral student writing - Kumar, Vijay; Aitchison, Claire (Teaching in higher education, 2018)
Very few empirical studies have investigated programmes in which doctoral students act as peer facilitators in faculty writing groups. We report on the development of a centrally delivered doctoral student writing programme in which twenty student participants were mentored and provided with the resources to initiate their own faculty-based doctoral writing groups. 'Legitimate peripheral participation' was used as a conceptual lens to interpret the data collected during the establishment and evaluation of the programme. All student participants in the preparatory training course, which was developed in consultation with postgraduate students and research supervisors, went on to become doctoral writing peer facilitators of peer writing groups. Insights from seven of these showed how a well-structured and supportive programme harnessed the benefits of peer learning by bringing personal rewards to participants and building institutional capacity around doctoral research writing literacies.